Evaluation of a Preclerkship Learning Community Model for Delivering Clinical Skills Curriculum. (June 2019) - Roussel, Danielle; Anderson, Katherine; Glasgow, Tiffany; Colbert-Getz, Jorie M
Background: Medical schools are increasingly using learning communities (LCs) for clinical skills curriculum delivery despite little research on LCs employed for this purpose. We evaluated an LC model compared with a non-LC model for preclerkship clinical skills curriculum using Kirkpatrick's hierarchy as an evaluation framework. Methods: The first LC cohort's (N = 101; matriculating Fall 2013) reaction to the LC model was assessed with self-reported surveys. Change in skills and learning transfer to clerkships was measured with objective structured clinical examinations (OSCEs) at the end of years 2 and 3 and first and last clerkship preceptor evaluations; the LC cohort and the prior cohort (N = 86; matriculating Fall 2012) that received clinical skills instruction in a non-LC format were compared with Mann-Whitney U tests. Results: The LC model for preclerkship clinical skills curriculum was rated as excellent or good by 96% of respondents in Semesters 1 to 3 (N = 95). Across multiple performance domains, 96% to 99% of students were satisfied to very satisfied with their LC faculty preceptors (N varied by item). For the end of preclerkship OSCE, the LC cohort scored higher than the non-LC cohort in history gathering ( P = .003, d = 0.50), physical examination ( P = .019, d = 0.32), and encounter documentation ( P ⩽ .001, d = 0.47); the non-LC cohort scored higher than the LC cohort in communication ( P = .001, d = 0.43). For the end of year 3 OSCE, the LC cohort scored higher than the non-LC cohort in history gathering ( P = .006, d = 0.50) and encounter note documentation ( P = .027, d = 0.24); there was no difference in physical examination or communication scores between cohorts. There was no detectable difference between LC and non-LC student performance on the preceptor evaluation forms at either the beginning or end of the clerkship curriculum. Conclusions: We observed limited performance improvements for LC compared with non-LC students on the end of the preclerkship OSCE but not on the clerkship preceptor evaluations. Additional studies of LC models for clinical skills curriculum delivery are needed to further elucidate their impact on the professional development of medical students.